Optimizing Ultra-Low Sidelobe Level Radiation in Concentric Circular Array Antennas Using Evolutionary Algorithms - Thadikamalla, Nageswar Rao; Chidurala, Sudharani; Amara, Prakasa Rao (2024 IEEE Microwaves, Antennas, and Propagation Conference (MAPCON), 2024)
This paper describes the Ultra-Low Side Lobe Radiation of Concentric Circular Array Antenna, which employs evolutionary optimization techniques. Particle Swarm Optimization (PSO), which has gone through the prose inspired by the meta-heuristic algorithm, is employed to obtain the radiation beam pattern properties of a Concentric Circular Array Antenna, Far-Field radiation beam pattern generated. Current trending applications include next-generation wireless communications and the Internet of Things-the optimization variables to attain preferable radiation pattern characteristics of CCAA. The approach illustrated by 4, 6, 8 and 8, 1 0, 1 2 elements three rings of a concentric circular array antenna with and without a centre element. The obtained simulation results dissipated the domination of this address on the side lobe level, resulting in maximum reduction. By suppressing the side lobe level, undesired signals and interference signals in the same frequency band are suppressed. The results are justified; the PSO algorithm grasped lower side lobe level values compared with existing methods in previously published papers.